How diversity (that is included) can fuel innovation and engagement – and how sameness can be lethal. Issue 3 (11th June 2018) - Frost, Stephen
Abstract : Purpose: Conventional wisdom says that diverse organisations perform better. However, this is not always the case. Diverse teams that are not inclusive are unable to leverage their diversity, and thus will not reap its benefits. The purpose of this paper is to show that organisations that exhibit inclusive behaviour and inclusive leadership can leverage diversity to reap its multiple positive benefits. Design/methodology/approach: This paper draws on various examples from different sectors, including Kodak, the US Armed Forces and NASA, to analyse the effects of sameness on teams. It also draws on the author's own experience and the most recent peer-reviewed research to look at the effects of inclusive management, not just diversity. Findings: This paper shows that there is ample evidence that diverse teams often perform better, and that they only perform better when led inclusively. The combination of diverse teams and inclusive management can lead to increased innovation and productivity and better decision-making. Originality/value: This important reframing of the value of inclusion and not just diversity is insightful for the CEO and C-suite leaders, as well as essential for human resource managers or anyone who makes decisions about hiring, promotions or team composition.